THE IMPACT OF COVID-19 ON TOBACCO PRICES IN LOMBOK TIMUR - Muh Fahrurrozi; Mohzana Mohzana; Hary Murcahyanto; Muhammad Rapii (Gorontalo State University, 2023)
This study aims to determine how covid-19 affects the price of tobacco in the Jerowaru sub-district partially. This research is a type of descriptive quantitative research. The population in this study was 169 tobacco farmers in the Jerowaru sub-district. The sampling technique with random sampling with a sample size of 63. Data collection techniques using questionnaires. The data analysis technique used is simple linear regression analysis. The results of this study indicate that Covid-19 has no significant effect on the price of tobacco in the Jerowaru sub-district. This can be known as follows: (1) Based on the partial test (t test) it can be observed that the t value is 0.164 which is smaller than the t table of 1.999 (0.164 1.999). So it can be concluded that covid-19 has no significant effect on the price of tobacco in Jerowaru District; (2) Based on the simple regression test from the output the coefficient of determination (r square) is 0.000, which means that Covid-19 has no significant effect on tobacco prices because the value obtained is 0.000%. As for the lack of effect between covid-19 on tobacco prices, that is because covid-19 focuses on microorganisms or viruses infecting humans or those transmitted from one human to another, so covid-19 focuses on infecting humans instead of infecting tobacco plants.